Unfinished agenda or overtaken by events? Applying aid- and development-effectiveness principles to capacity development support - Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
This paper analyses to what extent the aid and development effectiveness agenda has been applied in the area of capacity development support, with a specific focus on the use of developing country systems. The paper is based on a literature review and a limited number of semi-structured interviews, as well as a review of available research evidence on capacity development support practices in Mozambique, Nepal, Rwanda and Vietnam. Three main conclusions are drawn from this paper. First of all, available research confirms that aid and development effectiveness achievements in the area of capacity development have been slow and disappointing, owing to reform-resistance of key stakeholders involved. Secondly, considerable potential remains to strengthen the effectiveness of capacity development support by further adapting approaches to design, deliver and evaluate interventions in reference to key aid and development effectiveness principles. Third, a lack of disaggregation of statistics and low investments in evaluation inhibits learning and accountability, and ultimately the improvement of capacity development results.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Entwicklungsfinanzierung und öffentliche Finanzen; Wirksamkeit und Evaluierung